A unique clonal JAK2 mutation leading to constitutive signalling causes polycythaemia vera - James, Chloé; Ugo, Valérie; Le Couédic, Jean-Pierre; Staerk, Judith; Delhommeau, François; Lacout, Catherine; Garçon, Loïc; Raslova, Hana; Berger, Roland; Bennaceur-Griscelli, Annelise; Villeval, Jean Luc; Constantinescu, Stefan N.; et al. (Nature (London), 2005)
Polycythaemia vera The basis of the bone marrow abnormality in polycythaemia vera, a blood disorder often linked to leukaemia, has finally been identified. Over 80% of patients have a mutation in the JAK2 enzyme; this normally stimulates red blood cell production when needed, after blood loss for example. The mutant enzyme is permanently in the ‘on’ position. The JAK2 mutation was also found in several other myeloproliferative disorders. With JAK2 as a possible target, it may be possible to develop targeted therapies similar to Glivec, now used to treat chronic myeloid leukaemia. Myeloproliferative disorders are clonal haematopoietic stem cell malignancies characterized by independency or hypersensitivity of haematopoietic progenitors to numerous cytokines 1 , 2 . The molecular basis of most myeloproliferative disorders is unknown. On the basis of the model of chronic myeloid leukaemia, it is expected that a constitutive tyrosine kinase activity could be at the origin of these diseases. Polycythaemia vera is an acquired myeloproliferative disorder, characterized by the presence of polycythaemia diversely associated with thrombocytosis, leukocytosis and splenomegaly 3 . Polycythaemia vera progenitors are hypersensitive to erythropoietin and other cytokines 4 , 5 . Here, we describe a clonal and recurrent mutation in the JH2 pseudo-kinase domain of the Janus kinase 2 ( JAK2 ) gene in most (> 80%) polycythaemia vera patients. The mutation, a valine-to-phenylalanine substitution at amino acid position 617, leads to constitutive tyrosine phosphorylation activity that promotes cytokine hypersensitivity and induces erythrocytosis in a mouse model. As this mutation is also found in other myeloproliferative disorders, this unique mutation will permit a new molecular classification of these disorders and novel therapeutical approaches.